Benteng Wuna: Tantangan Golongan Bangsawan Muna di Era Modern - Amin Langaja (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2024)
Fort Wuna as evidence of the residential separation of the Muna noble class shows that the social stratification system still applies in Muna even though many people still have middle to lower economic conditions. This research aims to find out what challenges are faced by the Muna noble class in the modern era with middle to lower economic conditions. The theory used in this research is Everyday Form of Resistance by James C. Scott. By using ethnographic methods, it was found that the Muna aristocrats who are in the middle to lower economic conditions must always maintain traditions by performing life cycle rituals that require a lot of money. The tactics used in overcoming these problems are by way of donations from relatives and superimposing their children in the procession of life cycle rituals carried out by other noble families.